(untitled) - Crawshaw, Laura (San Francisco, 2007)
Taming the Abrasive Manager is an ideal resource for managers, human resource professionals, coaches, and anyone who works for or with an abrasive boss. Executive coach Dr. Laura Crawshaw— known as the “Boss Whisperer” for her work in this field—shares her discoveries on how to tame the deep fears that drive abrasive managers to attack their coworkers. In her straight-shooting style, Crawshaw offers invaluable insights gained from her encounters with abrasive bosses in corporate jungles who aggressively defend against threats to their dominance in the high-risk business of survival. These insights, combined with lessons learned from employees and organizations who have successfully reined in their unmanageable bosses, provide realistic solutions that will improve the workplace for everyone.
Keywords: Managing your boss,Organizational behavior,Interpersonal relations,Quản lý sếp,Hành vi tổ chức,Quan hệ giữa các cá nhân